Assimilating flow and level data into an urban drainage surrogate model for forecasting flows and overflows. (15th October 2019) - S.V. Lund, Nadia; Madsen, Henrik; Mazzoleni, Maurizio; Solomatine, Dimitri; Borup, Morten
Abstract: It is crucial to be able to forecast flows and overflows in urban drainage systems to build good and effective real-time control and warning systems. Due to computational constraints, it may often be unfeasible to employ detailed 1D hydrodynamic models for real-time purposes, and surrogate models can be used instead. In rural hydrology, forecast models are usually built or calibrated using long historical time series of, for example, flow or level observations, but such series are typically not available for the ever-changing urban drainage systems. In the current study, we therefore used a fast, reservoir-based surrogate forecast model constructed from a 1D hydrodynamic urban drainage model. Thus, we did not rely directly on historical time series data. Forecast models should preferably be able to update their internal states based on observations to ensure the best initial conditions for each forecast. We therefore used the Ensemble Kalman filter to update the surrogate model before each forecast. Water level or flow observations were assimilated into the model either directly, or indirectly using rating curves. The model forecasts were validated against observed flows and overflows. The results showed that model updating improved the forecasts up to 2 h ahead, but also that updating using water level observations resulted in better flow forecasts than assimilation based on flow data. Furthermore, updating with water level observations was insensitive to changes in the noise formulation used for the Ensemble Kalman filter, meaning that the method is suitable for operational settings where there is often little time and data for fine-tuning. Highlights: The EnKF is suitable for updating the states of urban drainage surrogate models. Updating the surrogate model improves both throttle flow and overflow forecasts. Updating improves flow forecasts up to 2 h ahead compared to no update. Updating with level data instead of flow data results in the best flow forecasts. Data assimilation of water levels can be done without tuning of noise parameters.